Framing super typhoon Haiyan by Philippine and international online news sites - Canubas, Aletheia G. (The Philippine Journal of Development Communication, 2016)
This qualitative study used Framing Theory to surface the themes and rhetoric building toward frames used in the reportage of two local online news (bulatlat.com and Interaksyon.com) websites about Typhoon Haiyan, the so-called "deadliest natural disaster" that hit the Philippines in 2013 and killed more than 6,000 people. A total of 654 articles published from November 2013 to November 2014, covering the pre-, during-, and after-landfall phases of the typhoon, were analyzed.